Cortical Neurotransmitters Measured by Magnetic Resonance Spectroscopy Change Following Traumatic Brachial Plexus Injury - Ryckie G. Wade; Gráinne Bourke; Alexandra M. Olaru; Stephen R. Williams; David Shelley; Sven Plein; Robert D. Bains; James D. Bedford; Lucy E. Homer Newton; Chye Yew Ng; Laura Parkes; Caroline Lea-Carnall (Journal of Brachial Plexus and Peripheral Nerve Injury)
Introduction GABA (γ-aminobutyric acid) is the major inhibitory neurotransmitter in the brain. In response to injury within the central nervous system, GABA promotes cortical plasticity and represents a potential pharmacological target to improve functional recovery. However, it is unclear how GABA changes in the brain after traumatic brachial plexus injuries (tBPIs) which represents the rationale for this pilot study.